(untitled) (Revista Científica Compendium, 2018)
One of the products with most recognition in the academic community is the scientific article. For that, it is important for journals to have a high level of visibility. This is achieved through its presence in international catalogs and in Institutional Repositories (IR). The aim of this research was to determine the scientific production, in SaberULA, of the 67 researchers who are part of the Reward of Encouragement to the Researcher (classification 2015), who work for the Dr. Pedro Rincon Gutierrez Extension, of the University of Los Andes. The research was based in the quantitative approach complemented by the qualitative one. It was a documental work in which the researchers’ scientific production was analyzed, between January 2005 and September 2016, in the 90 specialized journals of this university. It was evidenced a lack of contribution with an average of 0.47 scientific article per year; also, a strong tendency to endogamy by some of the editors and members of editorial committees.